Social Media and Student Protest Mobilisation in South African Universities: A Review of Literature on Motivations and Limitations - Mutongoza, Bonginkosi Hardy; Hendricks, Eleanor Alvira (Research in Social Sciences and Technology, 2025)
South Africa is frequently referred to as the global protest capital because of recurring social uprisings, especially against poor service delivery. Student protests at South African universities have increasingly relied on social media for mobilisation, information dissemination and activism. This study employs a systematic literature review of 34 studies sourced from JSTOR, Google Scholar, Scopus, Web of Science, ERIC, and Taylor & Francis to examine the motivations, opportunities, and limitations of social media in student protest mobilisation. The findings indicate that students use social media for rapid information dissemination, broader reach, decentralisation, narrative control over mainstream media, and garnering global solidarity. However, key limitations include the risk of infiltration and misinformation, the persistence of the digital divide, unethical conduct, leadership and coordination deficits, and the short-lived nature of clicktivism. These findings contribute to the ongoing debates on the intersection of digital activism and student protests, raising critical considerations for policymakers and higher education stakeholders regarding the regulation of social media in the context of protest mobilisation.